DEMAND FORECASTING AND ANALYSIS OF TRANSSHIPMENT CARGO IN I GUSTI NGURAH RAI AIRPORT USING CAUSAL AND TIME SERIES METHOD - SHOFIAH HUMAIRAH, FITRI
absence of airports in Indonesia which entered into the top 10 in terms of the amount of cargo handling. In addition, Indonesia is not yet a player in the transshipment cargo business. Therefore, to assist in the formulation of policies, such as the determination of layout, warehouses, and tariffs, a demand analysis will be carried out related to existing demand and demand that will grow when transshipment is implemented. This study combines causal models (conjoint model), binary logistic regression models, and time series forecasting models (Holt Winters and ARIMA). Demand data were obtained from distributing conjoint questionnaires to airlines and cargo forwarders totaling 233 respondents at CGK, HLP, and DPS. This research produces potential market share of transshipment cargoes for each type of commodity along with the projected growth for the next 10 years. The results of the analysis and projected demand can be used as a basis in the development of policy recommendations and strategies set by the Indonesian government and related stakeholders, such as determining the area and layout of the warehouse, the needs of facilities and human resources, as well as economic analysis to determine total costs and benefits to be gained. The results of this study indicates that the accuracy of cargo shipping, cargo security, customs document service speed, airport connectivity, and cargo loading and unloading speed will affect consumer preferences for transshipment cargo services. In addition, it is found that the total transshipment cargo demand is 204.023 tons for the first year with an average growth of 0,74% per year.